The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1183/13993003.01626-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with chronic thromboembolic pulmonary hypertension

Abstract: Patients with chronic thromboembolic pulmonary hypertension (CTEPH) experience debilitating symptoms that have a negative impact on their quality of life (QoL) in terms of physical capability, psychological wellbeing and social relationships. The use of QoL measurement tools is important in the assessment of treatment efficacy and in guiding treatment decisions. However, despite the importance of QoL, particularly to the patient, it remains under-reported in clinical studies of CTEPH therapy. CTEPH is unique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 70 publications
3
59
0
1
Order By: Relevance
“…25 It has been reported that patients with PH have debilitating symptoms that negatively impact HRQoL, which mainly generates a progressive deterioration in physical capacity and psychological status. 32 These statements are very similar to those found in our study because the patient presented greater problems in the fatigue and dyspnea domain of the CRQ-SAS questionnaire, clearly evidencing the commitment in the respiratory physical capacity. In turn, as mentioned by some authors, the interventions based on aerobic exercise, muscle strengthening of upper and lower limbs and respiratory muscle exercises, have clear benefits in the quality of life of patients with pathology of pulmonary origin, 33 which benefits for patients, not only in the domains related to the symptomatology, but also in the emotional domains and the control of the disease (Table 2).…”
supporting
confidence: 78%
“…25 It has been reported that patients with PH have debilitating symptoms that negatively impact HRQoL, which mainly generates a progressive deterioration in physical capacity and psychological status. 32 These statements are very similar to those found in our study because the patient presented greater problems in the fatigue and dyspnea domain of the CRQ-SAS questionnaire, clearly evidencing the commitment in the respiratory physical capacity. In turn, as mentioned by some authors, the interventions based on aerobic exercise, muscle strengthening of upper and lower limbs and respiratory muscle exercises, have clear benefits in the quality of life of patients with pathology of pulmonary origin, 33 which benefits for patients, not only in the domains related to the symptomatology, but also in the emotional domains and the control of the disease (Table 2).…”
supporting
confidence: 78%
“…CTEPH patients experience debilitating symptoms that severely impact their life quality. 39 Figure 6 demonstrated the effect of PAH-specific treatments on Borg dyspnea scale in this population, which was reported in four studies. [8][9][10]13 There was a larger improvement with PAH-targeted therapies, as compared to control (MD, −0.70; 95% CI, −1.08 to −0.32; P < 0.001).…”
Section: Clinical Symptomsupporting
confidence: 59%
“…CTEPH patients experience debilitating symptoms that severely impact their life quality . Figure demonstrated the effect of PAH‐specific treatments on Borg dyspnea scale in this population, which was reported in four studies .…”
Section: Resultsmentioning
confidence: 66%
“…The second study in patients with PAH also identified a significant deterioration in FC associated with a prolonged time between patient-described symptom onset and diagnosis of PAH by right heart catheterisation, which the authors considered could potentially impact on mortality [69], although it should be considered that the natural history of PAH is not the same as that of CTEPH. The consequence of late diagnosis is that treatment options may become limited due to comorbidities and organ damage, and the patient's quality of life may be severely compromised [70]. There appeared to be regional variations in the numbers of patients in NYHA FC III/IV at diagnosis in this study, particularly between Japan and Europe.…”
Section: Discussionmentioning
confidence: 74%